Is Negotiation Training Important when Dealing with Chinese Business People - An Analysis of Managers’ Beliefs and Needs in Three Countries - Zhu, Xiaoshu; Gao, Chang (Intercultural Communication Studies, 1970)
Is Negotiation Training Important when Dealing with Chinese Business People - An Analysis of Managers’ Beliefs and Needs in Three Countries